If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4cosx + -2sinx = 2 Solving 4cosx + -2insx = 2 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2insx' to each side of the equation. 4cosx + -2insx + 2insx = 2 + 2insx Combine like terms: -2insx + 2insx = 0 4cosx + 0 = 2 + 2insx 4cosx = 2 + 2insx Divide each side by '4osx'. c = 0.5o-1s-1x-1 + 0.5ino-1 Simplifying c = 0.5o-1s-1x-1 + 0.5ino-1 Reorder the terms: c = 0.5ino-1 + 0.5o-1s-1x-1
| 5y+4(-y-4)=-11 | | 8x-(x-5)=x+25 | | -36=2v+2(v-4) | | -7X+2+X=-16 | | 16x+4=5x-6x | | 2x+2y-2y= | | 3y-y+5y-(-2y)=-108 | | 2=-4(2x-9)+6x | | 16=X+8+2 | | (0.5x-4)-(1.5x+2.3)= | | 19x-8=12x-43 | | 12(4+n)+5(-2n-9)=1 | | 5a+8-4=-21 | | 116=-4x+2(-5x-5) | | 12x^2-96x+0=0 | | 13x=-7x+6*5 | | 110+.60x=70+.80x | | 4xy^3*7x^2y^3= | | 3(-4-2)-7=-85 | | 5+12=2z | | 17=9x+5-x | | x=60+0.50*125 | | 5x-mx=w | | 5x-7=1x-4 | | 2x/5-4=7x-8 | | 12x^2-96x=0 | | -3f+3(-3f+5)= | | -3-21x=-8x-8 | | 64-32x=80 | | 55=6a-7 | | 2xy+2x=55 | | 7x^2+4x-40=0 |